2020
DOI: 10.3390/catal10101162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesostructured Zirconia Support on the Activity and Selectivity of 4,6-Dimethydibenzothiophene Hydrodesulfurization

Abstract: In contrast with the conventional CoMoS/alumina catalyst, the use of amorphous mesostructured ZrO2 as support for the dispersion of the CoMoS active phase in deep hydrodesulfurization (HDS) of 4,6-dimethyldibenzothiophene led to a higher promotion rate and a better sulfidation of the cobalt species. The CoMoS, dispersed over mesostructured amorphous ZrO2 as catalyst, also induced a modification of the main desulfurization way; in this case, a shift towards direct desulfurization selectivity was observed. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The Zr 3d photoelectron peaks (Figure S6) were observed for the two samples: for Ni/35AZ - at 182.7 and 185.16 eV, for Ni/65AZat 181.1 and 183.6 eV. These values correspond to Zr 3d 5/2 and Zr 3d 3/2 , respectively, which are assigned to the +4 oxidation state of the zirconium. The O 1s photoelectron peaks of Ni/35AZ and Ni/65AZ samples were deconvoluted in four peaks at 528, 530, 531, and 532.5 eV (Figure ), which were attributed to lattice oxygen (O L ) < 530 eV, oxygen vacancies (O V ) ∼531 eV, and chemically adsorbed oxygen species (O C ) 532.5 eV, respectively. The oxygen vacancy ratios were calculated using the formula O V /(O V + O L ) (Table ). For the reduced Ni/35AZ and Ni/65AZ samples, the oxygen vacancy ratios were found to be 0.660 and 0.642, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The Zr 3d photoelectron peaks (Figure S6) were observed for the two samples: for Ni/35AZ - at 182.7 and 185.16 eV, for Ni/65AZat 181.1 and 183.6 eV. These values correspond to Zr 3d 5/2 and Zr 3d 3/2 , respectively, which are assigned to the +4 oxidation state of the zirconium. The O 1s photoelectron peaks of Ni/35AZ and Ni/65AZ samples were deconvoluted in four peaks at 528, 530, 531, and 532.5 eV (Figure ), which were attributed to lattice oxygen (O L ) < 530 eV, oxygen vacancies (O V ) ∼531 eV, and chemically adsorbed oxygen species (O C ) 532.5 eV, respectively. The oxygen vacancy ratios were calculated using the formula O V /(O V + O L ) (Table ). For the reduced Ni/35AZ and Ni/65AZ samples, the oxygen vacancy ratios were found to be 0.660 and 0.642, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Many studies have shown that the activity and selectivity of the catalysts are correlated not only to the reducibility, size and arrangement of the active phase but also are significantly influenced by the acidic properties of the carriers, especially Brønsted acidity [11,12]. Moreover, many studies have tried to improve the performance of hydrotreating catalysts by doping the alumina support with acidic agents, such as fluorine, boron, phosphorus, and zeolites [13,14]. The catalytic performance of the conventional HDS catalysts can be modified by replacing the alumina with other materials, leading to an important improvement of the HDS activity.…”
Section: Introductionmentioning
confidence: 99%